2020
DOI: 10.1111/pim.12703
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant elongation factor 1 alpha of Haemonchus contortus affects the functions of goat PBMCs

Abstract: Excretory/secretory proteins of Haemonchus contortus (HcESPs) intermingle comprehensively with host immune cells and modulate host immune responses. In this study, H contortus ES antigen named as elongation factor 1 alpha (HcEF‐1α) was cloned and expressed. The influences of recombinant HcEF‐1α on multiple functions of goat peripheral blood mononuclear cells (PBMCs) were observed in vitro. Immunoblot analysis revealed that rHcEF‐1α was recognized by the serum of goat infected with H contortus. Immunofluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
(97 reference statements)
0
5
0
Order By: Relevance
“…Previous studies have shown that various HcESP-derived protein molecules, such as rHcMTF-12 [ 54 ], rHCRD [ 37 ], rHc-GDC [ 40 ], rHcEF-1α [ 46 ], rHcES-15 [ 34 ], rMiro-1 [ 55 ], HCcyst-3 [ 56 ] and RHC-AK [ 57 ], can bind to PBMCs in vitro and regulate cellular immune function. Our studies showed that rHcGOB can bind to goat PBMCs and activate the IL-10/TGF-β/STAT3 pathway in PBMCs in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that various HcESP-derived protein molecules, such as rHcMTF-12 [ 54 ], rHCRD [ 37 ], rHc-GDC [ 40 ], rHcEF-1α [ 46 ], rHcES-15 [ 34 ], rMiro-1 [ 55 ], HCcyst-3 [ 56 ] and RHC-AK [ 57 ], can bind to PBMCs in vitro and regulate cellular immune function. Our studies showed that rHcGOB can bind to goat PBMCs and activate the IL-10/TGF-β/STAT3 pathway in PBMCs in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional levels of mRNA were detected by qPCR, and the β-actin gene was used as the reference gene. In accordance with a previous study [ 46 ], the primer sequences shown in Additional file 1 : Table S2 were used. The calculation was carried out according to the comparative Ct (2 −ΔΔCt ) method.…”
Section: Methodsmentioning
confidence: 99%
“…The reaction system contained 5 μl 2× ChamQ SYBR qPCR Master Mix (Vazyme Biotech Co., Ltd.), 3.6 μl ddH 2 O, 0.2 μl forward and reverse primers and 1 μl cDNA. Primer sequences are shown in Additional file 1 : Table S2 [ 23 , 24 ]. To calculate raw cycle thresholds (Ct), the relative Ct (2 −ΔΔCt ) method was used with ABI Prism 7500 software (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…The monocytes were separated from freshly collected PBMCs, and washed with PBS (Ca 2+ /Mg 2+ -free, pH 7.4). Cells numbers were adjusted to 1 × 10 5 cells/ml in RPMI-1640 supplemented with 10% FBS, 100 U/ml penicillin and 100 mg/ml streptomycin (Gibco Life Technologies); then incubated with rFg-CaBP4, or control buffer, at 37 °C in 5% CO 2 for 2 h. Protein binding was examined using an immunofluorescence assay [ 34 ]. The monocytes were washed and added to poly- L -lysine-treated slides, fixed with 4% paraformaldehyde for 30 min and permeabilized with 1% Triton X-100/PBS.…”
Section: Methodsmentioning
confidence: 99%